Massive Open Online Courses as enablers of service learning - Dominik E. Froehlich; Sophie Wührl; Ulrich Hobusch (Forum Neue Medien in der Lehre Austria, 2023)
MOOCs offer the possibility of flexible and independent learning processes. Using MOOCs at universities is often seen in the context of blended learning and inverted learning. But the use of MOOCs in other didactic formats, such as service-learning, is less common. Service-learning describes the combination of social engagement with the training of students, i.e., the teaching of technical, methodological and social skills. The aim of this article is to reflect on the use of MOOCs in service-learning and to provide suggestions for further research